ISLAMIC PRINCIPLES ON KHITBAH AND COURTSHIP VERSUS THE EFFECTS OF SOCIAL MEDIA ON MUSLIM MARRIAGES IN NORTHERN NIGERIA - Alhaji Rabiu, Aliyu; Ibrahim, Dahiru Inuwa; Sa’ad, Jaafar (Jurnal Syariah, 2019)
Khitbah and Courtship are part of the foundational stages for the formation of a matrimonial home which largely depend on the moral climate of a given society at a particular time. It is a volatile stage in which people make or mar their matrimonial lives. As marriage proposal and steps taken by prospective couples to understand one another better, are practices approved by the Shariah with prescribed ethical principles. However, these noble acts are observed to be bastardized by modern young prospective Muslim couples in northern Nigeria which in the short or long-run affect the socio-moral standing of the matrimonial home and in some ways, even the children to be born as well as the larger society. Perceptibly, gross abuse of the social media platforms and blind imitation of some ill-western traits in courtship coupled with unnecessarily longer courtship period are the identifiable factors that challenge the Shariah-based rule of courtship behavior in contemporary times. Therefore, the paper discussed Shariah provisions on khitbah and courtship while highlighting how some potential Muslim couples in Northern Nigeria are deviating from this guidance which ultimately affect the family institution as a social fabric of the society. Considering the theoretical and empirical nature of this study, both qualitative and quantitative methodologies were used in data collection, analysis and presentation. The results of the research showed that there are abuses and malpractices in khiá¹bah and courting behavior by to be couples and their families which adversely affect the moral standing of matrimonial homes and the larger society. It is recommended that, Muslim youth and their parent should adhere strictly to the Shariah rules on khitbah and courtship and formal pre-marital counseling centers should be established by Masajid and Muslim organizations to help address the situation.